Implementing changes to reduce infections in ICU patients. Water services and waste systems. Issue 2 (March 2023) - Weinbren, Michael; Inkster, Teresa; Walker, Jimmy
Background: Evidence linking the role of water services in transmission of infection to patients in ICUs has increased in recent years. Aims: This research based commentary set out to identify potential solutions for water and wastewater systems in ICU settings. Methods: Databases and open source information was used to obtain data on approaches to water and wastewater-related issues in ICU settings. This and the authors experiences have been used to describe approaches to these problems. Findings: The lack of updated guidance has required some ICUs to develop unique responses, including 'water free' patient care combined with reduction in water services. The options consider guidance, compliance, training and education as key factors to successful outcomes and protecting vulnerable patients in ICU. Discussion: The authors found a number of problems with water and wastewater systems in ICU to which there has not been a cohesive response in terms of guidance to support users and designers. The resultant void permits new projects to proceed with suboptimal and designs which place patients and staff at risk. As an interim measure a series of solutions suitable for existing units and new builds need to be considered.